(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Indian legal system regarding child custody is primarily governed by the Guardians and Wards Act, 1890, and the Hindu Minority and Guardianship Act, 1956 and other religion specific Laws. These laws provide a framework for determining who should have custody of a child in case of separation or divorce. In India, the best interests of the child are considered the primary consideration when determining custody. The court may award custody to either the father or the mother, depending on various factors such as the financial stability of each parent, the age of the child, and the capability to provide a stable and loving environment for the child by each parent. Western countries, such as the United States, follow the principle of determining custody by considering the best interests of the child. In the US, the Uniform Child Custody Jurisdiction and Enforcement Act (UCCJEA) provides a framework for determining jurisdiction and enforcing custody orders across states.